Влияние музыки различных направлений на когнитивную деятельность человека - Чувурина, А.А.; Луценко, Е.Л. (My University, 2014)
The paper describes the features of influence of classic music, popular music, rock music and jazz on memory, intelligence, concentration of attention and creativity. It was also researched the relationships between the coefficient of intelligence and musical preferences of the person.
Keywords: музыкальные стили, музыкальные предпочтения, интеллект, внимание, креативность, память; психофизиология